Ressourcen in historischer Perspektive Landschaft, Literatur und Nachhaltigkeit - Schanbacher, Ansgar (Universitätsverlag Göttingen, 2020)
The use of resources is the precondition of all life. This is foremost true for natural resources such as water, food and fuels but also for immaterial resources like information and efficient social networks. In this book authors from different disciplines try to understand the dealing with resources in a historical perspective. Thereby they analyse topics such as the supply of food in classical Greece, the forest management in the Austrian Alps provinces of the nineteenth century, libraries as stores of knowledge and the present landscape as resource for a better understanding of the past. Together, the papers which are the result of a 2019 workshop of the Göttingen based research project "Nachhaltigkeit als Argument / Sustainability as an Argument" show the diversity and potentials of historical research in the field of resources.